Genome-wide identification and adaptive evolution of CesA/Csl superfamily among species with different life forms in Orchidaceae - Wang, Jingjing; Li, Jing; Lin, Wei; Deng, Ban; Lin, Lixian; Lv, Xuanrui; Hu, Qilin; Liu, Kunpeng; Fatima, Mahpara; He, Bizhu; Qiu, Dongliang; Ma, Xiaokai (Frontiers in Plant Science, 2022)
Orchidaceae, with more than 25,000 species, is one of the largest flowering plant families that can successfully colonize wide ecological niches, such as land, trees, or rocks, and its members are divided into epiphytic, terrestrial, and saprophytic types according to their life-forms. Cellulose synthase (CesA) and cellulose-like synthase (Csl) genes are key regulators in the synthesis of plant cell wall polysaccharides, which play an important role in the adaptation of orchids to resist abiotic stresses such as drought and cold. In this study, nine whole-genome sequenced orchid species with three types of life forms were selected; the CesA/Csl gene family was identified; the evolutionary roles and expression patterns of CesA/Csl genes adapted to different life forms and abiotic stresses were investigated. The CesA/Csl genes of nine orchid species were divided into eight subfamilies: CesA and CslA/B/C/D/E/G/H, among which the CslD subfamily had the highest number of genes, followed by CesA, whereas CslB subfamily had the least number of genes. Expansion of the CesA/Csl gene family in orchids mainly occurred in the CslD and CslF subfamilies. Conserved domain analysis revealed that eight subfamilies were conserved with variations in orchids. In total, 17 pairs of CesA/Csl homologous genes underwent positive selection, of which 86%, 14%, and none belonged to the epiphytic, terrestrial, and saprophytic orchids, respectively. The inter-species collinearity analysis showed that the CslD genes expanded in epiphytic orchids. Compared with terrestrial and saprophytic orchids, epiphytic orchids experienced greater strength of positive selection, with expansion events mostly related to the CslD subfamily, which might have resulted in strong adaptability to stress in epiphytes. Experiments on stem expression changes under abiotic stress showed that the CslA might be a key subfamily in response to drought stress for orchids with different life-forms, whereas the CslD might be a key subfamily in epiphytic and saprophytic orchids to adapt to freezing stress. This study provides the basic knowledge for further systematic study of the adaptive evolution of CesA/Csl superfamily in angiosperms with different life-forms, and research on orchid-specific functional genes related to life-history trait evolution.